Sejarah Politik Hukum Islam Dari Klasik Ke Kontemporer: Pengembangan Dan Transformasi - Rizani, Rasyid; Hasa, Ahmadi; Umar, Masyithah; Khasyi'in, Nuril (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This paper discusses the Classical Islamic political thought began with the Prophet Muhammad in Medina in 622 AD. After his death, the government was held by the Khulafa Rashidin, then the Bani Umayah and Abbasid dynasties. Political Islam entered the Middle Ages after the fall of the Abbasids. The Prophet Muhammad created a new perspective among Muslims. Three groups of Islamic thought were seen: Islam is a perfect religion, Islam has no political system, and Islam does not prepare a political system but does not leave Muslims without guidance. The Prophet's political steps in Medina included the construction of the mosque, the brotherhood of the Muhajirin and Anshar, and the charter of Medina. The caliphate government was led by the caliph, who was in charge of both politics and religion. The Qur'an and hadith were the basis of the caliphs' leadership, and they had the religious responsibility of implementing religious law. The research method used is the diachronic historical method Keywords: politics, law, and Islam. Abstrak Tulisan ini membahas tentang pemikiran politik Islam abad klasik dimulai dengan Nabi Muhammad saw. di Madinah pada tahun 622 M. Setelah wafatnya, pemerintahan dipegang oleh Khulafa Rasyidin, kemudian dinasti Bani Umayah dan Abbasiyah. Politik Islam memasuki abad pertengahan setelah kehancuran Abbasiyah. Nabi Muhammad saw menciptakan perspektif baru di kalangan umat Islam. Tiga kelompok pemikiran Islam terlihat: Islam agama sempurna, Islam tidak memiliki sistem politik, dan Islam tidak menyiapkan sistem politik tetapi tidak membiarkan umat Islam tanpa pedoman. Langkah politik Rasulullah saw di Madinah termasuk pembangunan masjid, persaudaraan kaum Muhajirin dan Anshar, dan piagam Madinah. Pemerintahan khilafah dipimpin oleh khalifah, yang memegang tampuk pemerintahan di bidang politik dan agama. Al-Qur'an dan hadis menjadi dasar kepemimpinan khalifah, dan mereka memiliki tanggung jawab agama dalam pelaksanaan hukum agama. Metode penelitian yang digunakan adalah metode historis diakronis. Kata kunci: politik, hukum, dan Islam